Entering the Classroom : Do Newcomers Experience More Peer Victimization than Their Established Peers? - Tenhunen, Essi-Lotta; Malamut, Sarah; McMullin, Patricia; Turunen, Tiina; Yanagida, Takuya; Salmivalli, Christina (Springer Science+Business Media, 2025)
Students changing classrooms or schools may face challenges from entering a new peer context without friends and standing out from the crowd as newcomers. Two studies examined whether newcomer status predicts peer victimization at school, exploring several potential moderating factors (e.g., social anxiety, immigrant background and having good friends in the classroom) (Study 1: n = 6,199; Mage=12.53) and whether being victimized as a newcomer varied based on the different reasons for mobility (e.g., parental dissolution, residential move, previous victimization, changing into a more suitable school) (Study 2: n = 58,738). In both studies, newcomers reported higher peer victimization compared to established students. Having good friends in the classroom was found as a protective factor in Study 1, being the only statistically significant moderator. All reasons for mobility, except changing into a more suitable school, predicted slightly higher peer victimization in Study 2, with the highest risk for those changing schools due to previous peer victimization experiences.